Khānaqāh : Mathnawi-yi ʿirfānī u akhlāqī bih payrawī az Būstān-i Saʿdī - Shīrāzī, Faqīr (Miras Maktoob, ISBN: 9789004365452., 2019)
In the history of the arts, emulation has always been important, regardless of time and place. Indeed, even the greatest artists always turn out to have their idols. Emulation is usually a way to acquire a certain skill or style that will then be put to use in the artist's own, original creations. Sometimes, emulation is such that the work of the original artist is still very present in the later work, mostly as a result of structural or stylistic similarities. In the field of Persian literature, a case in point is Jāmī's (d. 898/1492) Bahāristān , a work on morals that was written in imitation of Saʿdī's (d.691/1291-92) Gulistān . Similarly, the present work by Faqīr Shīrāzī (d. 1351/1932) is a successful reproduction of the style and format of Saʿdī's ethical mathnawī , the Bustān . Still, their content is quite different, Khānaqāh being an ode on mysticism and the Bustān a poem on ethics.